Virtual Art Therapy for Adolescence Mental Health Education: Systematic Literature Review and Future Perspectives - Dody Hartanto; Mufied Fauziah; Remedios C. Moog; Yenni Rizal; Diki Herdiansyah; Nuri Cholidah Hanum (Universitas Muhammadiyah Surakarta, 2025)
This study aims to conduct a systemic literature review on the application of virtual art therapy as an effort to maintain adolescent mental health and examine the use of mental health services in the future by utilizing technology. The research was conducted using a systematic literature review on scientific articles. Seven key studies were selected as the primary sources to describe the application of virtual art therapy as an effort to maintain adolescent mental health. Selected articles were analyzed by data extraction. The findings indicate the application of virtual art therapy for adolescents in maintaining mental health as a complex process by utilizing the deepest human feelings that is hard to be expressed by words. Virtual art therapy was done by mediating what the client expresses through art created in the virtual world. The aesthetics art made was not the main focus of the therapeutic process, but the way the art can be realized as an expression of feelings. In future research, there needs to be an effort to develop and test the success of virtual art therapy models in creating mental health and conduct empirical surveys to assess the suitability of virtual art therapy models among adolescents.